DIGITALISASI BUDAYA BALI: MEDIA AR SEBAGAI BENTUK REVITALISASI AKSARA BALI - NURHUDA, TRIFALAH; PURNAMI, IDA AYU PUTU; WISNU, I WAYAN GEDE; JONIARTA, I MADE (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2024)
Balinese script is one of the cultural heritages of the Balinese people that has become increasingly marginalized in today's era of globalization. This study aims to design and evaluate Augmented Reality (AR)-based learning media as a form of cultural revitalization for Bali. The research was conducted using the ADDIE development model (Analyze, Design, Development, Implementation, Evaluation) to create interactive learning media tailored to the needs of students and teachers. The results of the study indicate that the Balinese Script AR media significantly enhances students' interest and understanding of Balinese script, receiving an average rating of